جماليات التصوير الفني بين تجليات مفهوم الصورة ودورها - بوخضرة حفصية; معيفي عبد الحميد (University of Eloued جامعة الوادي, 2025)
تعد الصورة الشعرية ملمحا أساسيا قادرا على أن يعطي للنص أبعادا دلالية، كما تُعتبر الميزان التفاضلي الذي يقيس به النقاد مدى إبداعية شاعر عن آخر، فهي بمثابة السلك الذي يشد حبات العقد بجعلها أكثر تناسقا، ولهذا يهتم النقاد بها، فهم على دراية بأنها ملاذ الشاعر فمن خلالها يصبح مصورا، فإلى أي مدى يكون للصورة الشعرية أثرها الجمالي وبعدها الإيحائي في النص؟، وإلى أي مدى تكون لصاحبها نظرته الثاقبة من خلال توظيفها؟، وله القدرة على الجمع بين المتناقضات، ولذلك قمنا بالسباحة في شاطئ مفهومها ووظيفتها ومحاولة الكشف عما يتركانه من أثر في نفسية المتلقي، لنتوصل إلى ما يلي: لا غنى للشاعر عن الصورة لأنها الملاذ والمقر الذي من خلاله ينطلق لمواجهة العالم بأسره، ــ يفرض الإبداع الشعري جعل الصورة الشعرية وسيلة وهدفا، لتكون بذرة مثمرة، فتمثل القصيدة بواقعها الذي تتجلى فيه في زمان ومكان محددين. The poetic image is a fundamental feature capable of giving the text semantic dimensions. It is also considered the differential scale by which critics measure the creativity of one poet against another. It is like the thread that tightens the beads of a necklace, making them more harmonious. This is why critics pay attention to it, as they are aware that it is the poet's refuge, through which he becomes a painter, To what extent does the poet possess a keen insight through its employment, and the ability to reconcile contradictions? Therefore, we swam in the shore of its concept and function, attempting to uncover the impact they leave on the recipient's psyche, leading us to the following conclusions: The poet cannot do without the image because it is the refuge and the base from which they embark to face the entire world. Poetic creativity necessitates making the poetic image both a means and an end, so it becomes a fruitful seed, representing the poem in its reality, which manifests in a specific time and place.
مقال . مجلة العلوم العربية
Keywords: جماليات؛ التصوير الفني؛ مفهوم الصورة؛ دورها.